Modelling the spatial bound of an eDNA signal in the marine environment – the effect of local conditions - Silva, Tiago A. M.; Beraud, Claire P. C.; Lamb, Philip D.; Rostant, Wayne; Tidbury, Hannah J. (Frontiers in Marine Science, 2025)
Environmental DNA (eDNA) is a powerful technique for biological assessments and monitoring in aquatic environments. The accurate interpretation of the source of eDNA detected requires understanding of its spatial and temporal bound. Studies which estimate eDNA dispersal in the aquatic environment, in particular the marine environment, are scarce and seldom represent the effect of hydrodynamics and eDNA decay. This study modelled eDNA dispersal in a coastal environment under diverse environmental conditions to assess how these conditions influence dispersal patterns. A modelling experiment shows that under thermally stratified conditions sampling eDNA across this gradient reduces detectability. Statistical analysis shows that both median and extreme eDNA dispersal distances simulated by the model were primarily controlled by local tidal conditions (tidal excursion), followed by month (influencing the water temperature and thus eDNA decay rate). The median distance varies between 2.27 and 14.14 km which falls within the range of previously published model results, and is up to 10x greater than observed values. However this gap has been narrowing, and the present statistical model helps set limits on the distance to source as a function of regional oceanography and water temperature. The present method can also be used post-survey to help interpret the location and number of sources. This study constitutes an advance in modelling eDNA dispersal in coastal areas and crucially provides much needed evidence to underpin robust interpretation of eDNA monitoring data and to inform the design of eDNA monitoring programmes that account for variable environmental conditions.